Safety and health of shrimp fishermen in Bertioga-São Paulo/Brazil: A study focused on atmospheric risk factors - de Souza, Gilmar Ortiz; Bitencourt, Daniel Pires (Sociedade & Natureza, 2019)
The risk of accidents during oceanic fishing is often high and it can cause several harms, from small injuries to death by drowning. The risks to fishermen’s safety and health are potentiated by atmospheric factors such as storms, wind, solar radiation, humidity, heat and cold waves, among others. Fishing is one of the most dangerous labour activities; therefore, it demands constant adjustments in its standards, procedures and public policies. The aim of the present study is to assess the work conditions of a group of fishermen based on atmospheric risk factors in order to contribute to measures taken towards these issues in Brazil. A questionnaire was answered by 20 shrimp fishermen from Bertioga-SP; it was the tool adopted to identify control measures taken by them in order to prevent accidents and diseases. Based on the results, these fishermen work under precarious work conditions and face high vulnerability, as well as the risk of accidents and of catching diseases. Moreover, results have shown that atmospheric factors have significantly contributed to increase such risks. In addition, these precarious work conditions have been worsened by the absence of safety adequate methods, as well as of preventive and emergency measures.